2006
DOI: 10.1002/bjs.5264
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing surgery with conservative treatment for uncomplicated varicose veins

Abstract: Surgical treatment provides symptomatic relief and significant improvements in quality of life in patients referred to secondary care with uncomplicated varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 14 publications
3
86
0
5
Order By: Relevance
“…So, analysis of the treatment undergone by the patient with emphasis on the complication and recurrence rate showed that the patients undergoing surgical treatment had better prognosis than the patients undergoing conservative line of treatment. This result was in complete agreement with the study of Michaels et al 11 which concluded that patients of uncomplicated varicose veins undergoing surgical management had a definitely better prognosis than patients undergoing conservative treatment. Comparing the surgically and the conservatively managed patients of this study, the complications of the surgical line of treatment were minor in nature and did not require any additional treatment and did not involve much additional discomfort to the patient.…”
Section: Discussionsupporting
confidence: 92%
“…So, analysis of the treatment undergone by the patient with emphasis on the complication and recurrence rate showed that the patients undergoing surgical treatment had better prognosis than the patients undergoing conservative line of treatment. This result was in complete agreement with the study of Michaels et al 11 which concluded that patients of uncomplicated varicose veins undergoing surgical management had a definitely better prognosis than patients undergoing conservative treatment. Comparing the surgically and the conservatively managed patients of this study, the complications of the surgical line of treatment were minor in nature and did not require any additional treatment and did not involve much additional discomfort to the patient.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3] While compression remains an important method for treating venous ulcers, interventional treatments for varicose veins due to superficial venous insufficiency (SVI) offer significantly greater benefit in health related quality of life compared to compression treatment alone, with the additional benefit of avoiding the need for long-term compression. 4,5 Traditionally, SVI has been effectively treated with open surgery, but ultrasound guided foam sclerotherapy (UGFS) and endothermal ablation with radiofrequency (RFA) and endovenous laser (EVLA) have become widely adopted. These local anaesthetic techniques have revolutionised the management of SVI, offering ambulatory out-patient treatment with minimal recovery time, and similar improvements in health-related quality of life as are seen following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that losses to follow-up are higher when no treatment is needed after surgery, especially when a longer follow-up period with no specific treatment is required. 2,8 The threats to credibility and validity of the trial are most prominent when there are systematic differences between comparison groups in the losses to follow-up or when there is attrition bias (i.e., withdrawals from the study). 2,6,7 The differential loss to follow-up is greater when concomitant interventions, such as rehabilitation or physiotherapy, are required postsurgery for 1 group, but not the other.…”
Section: Methodological Impact Of Loss To Follow-upmentioning
confidence: 99%
“…2,6,7 The differential loss to follow-up is greater when concomitant interventions, such as rehabilitation or physiotherapy, are required postsurgery for 1 group, but not the other. 2,8 When comparing a surgical treatment to a medical treatment, there is a significant chance of attrition owing to participants who fail to attend follow-up visits or withdraw from the trial in the medical group owing to dissatisfaction with their treatment option. 8 Michaels and colleagues 8 conducted an RCT to compare surgery with conservative treatment for uncomplicated varicose veins.…”
Section: Methodological Impact Of Loss To Follow-upmentioning
confidence: 99%
See 1 more Smart Citation